Investigation of the role of curcumin against the toxicity induced by bisphenol a on the reproductive system in male rats - Rasool , Majid Hamid; Al-Nuaimi, Ali J.; Al-Sabbagh, Juman Khaleel (Journal of Kerbala for Agricultural Sciences, 2024)
Bisphenol A (BPA) is an endocrine disruptor and an environmental pollutant; it can produce free radicals, which cause damage in various tissues. Curcumin has been demonstrated to help with a variety of male reproductive diseases, as well as to scavenge free radicals and function as an antioxidant. The aim is to estimate the protective role of Curcumin against the toxic effect of BPA in male rats by determining the levels of antioxidants and sexual hormones, before and after treatment with this herb. The effect of curcumin as a protective role against BPA on the oxidative stress parameters showed that Curcumin could decrease MDA concentration and at the same time increase the concentration of both catalase and SOD. Also, the results revealed that Curcumin could increase the concentration of LH, FSH, and testosterone as compared to the BPA-treated group.